Influence of Sambo Wrestling Training on Students' Physical Fitness - Grygoriy Griban; Dmytro Dzenzeliuk; Zoia Dikhtiarenko; Eduard Yeromenko; Andrii Lytvynenko; Olena Otravenkoa; Bogdan Semeniv; Volodymyr Prystynskyi; Kostiantyn Prontenko (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
Concerning the low level of physical fitness of Ukrainian students and insufficient motivation to do physical exercises, one potential solution is the implementation of specific sport-oriented physical education classes, taking into account students' choice of sport. The influence of sambo (self-defence without arms) wrestling training on the level and dynamics of students' physical fitness when studying at higher educational institutions is examined in the article. The investigation of students' physical fitness was conducted according to the following tests: 100-metre race, pull-ups (male), push-ups (female), 3000-metre race (male), 2000-metre race (female), shuttle run 4 × 9 m, sit-ups (per 1 min), standing long jumps, forward inclinations of the body in sitting position. The significantly better (p<0.05-0.001) physical fitness level of students who were involved in the sambo wrestling training during studying in comparison with students who were involved in the current system of physical education was determined, which proves the efficiency of sambo wrestling training. The improvement of students' physical fitness during sambo wrestling classes will have a positive influence on their physical working capacity and the efficiency of their studying and future professional activities.